2000
DOI: 10.1161/01.cir.102.2.260
|View full text |Cite
|
Sign up to set email alerts
|

Widening of the Excitable Gap During Pharmacological Cardioversion of Atrial Fibrillation in the Goat

Abstract: Pharmacological cardioversion of AF cannot be explained by prolongation of WL(AF). An alternative explanation for the antifibrillatory effect of class I and III drugs may be a widening of the temporal excitable gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
182
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(201 citation statements)
references
References 32 publications
(29 reference statements)
16
182
0
3
Order By: Relevance
“…However, in 2 horses the termination times were strikingly short and correlated with very limited increases in AFCL, indicating a questionable drug‐related termination of AF. However, in the majority of horses, the flecainide‐induced increase in AFCL corresponded well with results reported by others 2, 17, 24, 27. A single study investigating flecainide‐induced changes in AFCL in horses with spontaneous AF reported comparable increases, nevertheless none of the treated horses cardioverted in response to treatment 2.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, in 2 horses the termination times were strikingly short and correlated with very limited increases in AFCL, indicating a questionable drug‐related termination of AF. However, in the majority of horses, the flecainide‐induced increase in AFCL corresponded well with results reported by others 2, 17, 24, 27. A single study investigating flecainide‐induced changes in AFCL in horses with spontaneous AF reported comparable increases, nevertheless none of the treated horses cardioverted in response to treatment 2.…”
Section: Discussionsupporting
confidence: 91%
“…Still, despite the lack of aERP prolongation at the atrial rates measured in the present study, we cannot rule out possible increases in aERP during the rapid rates typical of AF. Our observations are in agreement with results from studies conducted in goats where aERP was unaffected, AFCL increased, and AF vulnerability unchanged by flecainide 17, 24. The variable flecainide‐induced changes in aERP may be related to species differences and species‐specific atrial ion channel composition.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations